Zonasi Kerentanan Likuifaksi Berbasis Liquefaction Potential Index (LPI) di Kecamatan Seberang Musi, Kabupaten Kepahiang - Qotrunnada, Mutia; Mase, Lindung Zalbuin; Supriani, Fepy; Azzahra, Raisya; Lubis, Aminah Rahmadhani; Misliniyati, Rena; Amri, Khairul (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2026)
This study aims to evaluate and map earthquake-induced liquefaction potential in Kandang and Temdak Villages, Seberang Musi District, Kepahiang Regency. The analysis integrates geotechnical and seismic parameters, including peak ground acceleration, shear wave velocity, earthquake intensity, and soil vulnerability index. The results indicate that the study area is dominated by high ground acceleration and strong to very strong shaking intensity, which act as the main triggering factors of liquefaction. The evaluation of subsurface conditions shows that liquefaction potential mainly occurs in shallow layers composed of loose and saturated soils, while deeper layers tend to be more stable. The liquefaction potential index values vary significantly, ranging from low to very high across different locations. The highest value reaches 76.04, indicating very high liquefaction potential, while the lowest value is approximately 4.45, indicating lower potential. These findings suggest that the thickness and dominance of vulnerable layers at shallow to intermediate depths are the main factors controlling liquefaction potential. Overall, the applied approach provides a representative assessment for identifying liquefaction-prone zones and supports earthquake risk mitigation planning in the study area.